2020
DOI: 10.1111/jav.02475
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably similar migration patterns between different red‐backed shrike populations suggest that migration rather than breeding area phenology determines the annual cycle

Abstract: The regular fluctuation of resources across the Globe guides movements of migratory animals. To ensure sufficient reproductive output and maintain viable population sizes, migratory animals should match arrival at breeding areas with local peaks in resource availability. It is generally assumed that breeding phenology dictates the timing of the annual cycle, but this is poorly studied. Here, we use light-level geolocator tracking data to compare the annual spatiotemporal migration patterns of a longdistance mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Birds of the Shrike family (Laniidae) exhibited faster spring migration speeds compared to autumn migration, and their selection of stopover sites tends to favor areas with abundant vegetation. During spring migration, these birds adopt a strategy that minimizes time spent in transit, aiming to reach their breeding grounds quickly and aligning with the peak of vegetation coverage upon arrival [50][51][52]. Research has indicated common cuckoos tend to initiate its migration approximately a month later than its parasitic host [53].…”
Section: Discussionmentioning
confidence: 99%
“…Birds of the Shrike family (Laniidae) exhibited faster spring migration speeds compared to autumn migration, and their selection of stopover sites tends to favor areas with abundant vegetation. During spring migration, these birds adopt a strategy that minimizes time spent in transit, aiming to reach their breeding grounds quickly and aligning with the peak of vegetation coverage upon arrival [50][51][52]. Research has indicated common cuckoos tend to initiate its migration approximately a month later than its parasitic host [53].…”
Section: Discussionmentioning
confidence: 99%
“…The same increase in synchrony towards the arrival date at the non‐breeding site was also revealed in our literature review for all previously tracked populations. Since the non‐breeding sites of all birds are centred around Mali, the synchrony of arrival time might be the result of birds tracking the peak of resources in Mali (Thorup et al 2017, Pedersen et al 2020). This may be supported by the onset of more moderate temperatures temperature in Mali in mid‐October, providing good climatic conditions until February (Nicholson 2013).…”
Section: Discussionmentioning
confidence: 99%
“…First, timing of reproduction has a major influence on migration phenology, shifting the entire annual cycle with the onset of breeding (Conklin et al 2010, Briedis et al 2016, Gow et al 2019, Meier et al 2020). Second, birds continuously adjust timing to match resource availability along their routes (Thorup et al 2017, Pedersen et al 2020). The pattern that is used can be observed in individuals from latitudinally‐different breeding populations which share the same non‐breeding site.…”
Section: Introductionmentioning
confidence: 99%
“…Although long-distance migration has evolved in many taxonomic groups [26], geographical variation in the timing of annual cycles and carry-over effects have mainly been studied in single breeding populations of migratory birds [13,27,28], that use a single wintering area or multiple wintering areas at similar latitudes [11,12,15] or in multiple breeding populations that breed at similar latitudes [29]. Ideally, quantifying and testing the relative effects of breeding and wintering location on the timing of annual schedules and on carry-over effects requires substantial geographic variation in both breeding and wintering areas and mixing of individuals from different breeding populations within wintering areas and vice versa (weak migratory connectivity [30]).…”
Section: Introductionmentioning
confidence: 99%